The Implementation of Environmental Law Protection in Indonesia - Reda Manthovani (Faculty of Law, Merdeka University Surabaya, Indonesia, 2022)
The current condition of environmental law enforcement is not as expected. Environmental problems tend to accumulate, become complicated and even lead to threats to peace. Environmental law enforcement is still a bureaucrat/government discourse, not yet leading to concrete action. The government has also not synchronized economic, social and ecological elements in every development policy, so it is seen that many policies issued by the government are detrimental to environmental interests, such as the issuance of Government Regulation No. 1 of 2004 concerning the policy of granting mining concessions in protected forests, to 13 mining companies, where this provision is contrary to Law no. 41 of 1999 concerning Forestry which prohibits mining activities in protected forests. The lack of success in enforcing environmental law is also due to irregularities in the process of enforcing environmental law, this can be seen in the application of Article 30 (2) of Law no. 23 of 1997 concerning Environmental Management which states that the settlement of disputes outside the court as referred to in paragraph (1) does not apply to environmental crimes as stipulated in this law or in other words to environmental crimes cannot be resolved through ADR , but in practice the provisions of Article 30 (2) of Law no. 23 of 1997 concerning Environmental Management is often violated or deviated. From criminal politics, the increase in criminal acts in the environmental sector is due to, among other things, development projects and programs that are planned and implemented at the local, regional and national levels, ignoring/not paying attention to environmental factors, not based on accurate research and estimates of developments or crime trends both now and in the future. the purpose of this research is to find out how far the implementation of environmental protection laws is.